MULTI-LEVEL PROTECTION SYSTEM OF INFORMATION AND TELECOMMUNICATION NETWORKS AGAINST INFORMATION SECURITY THREATS BASED ON STRUCTURAL SEGMENTATION - DZIUBAN, OLEKSII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
In the modern information space, an information and telecommunication network is a key component of any organization's operations. Such a network enables the transmission, storage, and processing of various types of data, a significant portion of which is confidential or restricted. This may include employees’ personal information, financial documentation, strategic plans of the organization, and other data that are vital to the institution's functioning and may become targets for information attacks. Due to the continuous rise in cyber threats, the issue of information protection in networks becomes one of the most critical tasks ensuring the stable operation of the organization. This article is devoted to the analysis and description of a model of a protected information and telecommunication network for an organization, which takes into account the specific nature of modern information threats. The proposed model includes a clear segmentation of the information network into two main parts: an internal network containing server resources with confidential data, and an external network that hosts servers intended for public access. Separate protection means and levels are provided for each of these zones, including the use of firewalls, intrusion detection systems, antivirus tools, access control mechanisms, and information protection from unauthorized access. Special attention is paid to methods of assessing the security status of the network against external and internal attacks. The model ensures reliable and comprehensive protection of the organization's information network, guarantees the confidentiality, integrity, and availability of information, and can be applied to building information security systems in government, commercial, and private sectors.
Keywords: information security; network protection; information and telecommunication network; information attacks; multi-level protection system